The changing earth exploring geology and evolution - Monroe, James S. (James Stewart) 1938-; Wicander, Reed 1946-. (St. Paul, MN West, 1994)
Instructor's manual and test bank to accompany
Includes bibliographical references and index.
Keywords: Geology